Strengthen Health–Promoting Workplace Using Participatory Approach to Enhance Staff’s Health-Promoting Behaviours and Health Status in Boromarajonani College of Nursing - Prathumtone, Vannapa; Chenchob, Panarat; Rasiri, Somtakul; Teerapong, Nantawan (Journal of Health Science of Thailand, 2019)
The purposes of this research were to study the health status and health problems, conditions, health-promotion of engagement of personnel; and to develop a model to promote health behaviours of the personnel using participatory approach. It was conducted in 4 phases. The phases 1&2 were to assess the situation of health status and health promoting behaviours, and to develop a participatory health promotion model among 46 participants purposively recruited from Boromarajonani College of Nursing. The phase 3 involved further refinement of the model; and the phase 4 was for model testing and evaluation in 104 personnel. The study tools included (1) a medical instrument to measure health condition; (2) guideline for group discussion; (3) guideline for conversational exercise to evaluate the model; (4) stress measurement form; and (5) topics for collecting lessons learnt. Data were analyzed by using descriptive statistics and content analysis. It was found that the majority of personnel were at moderate risk of non-communicable diseases, obesity, waist circumference, high blood pressure, high blood sugar, high blood cholesterol, and high level of stress. For the health promotion model development, 4 steps were applied which included (1) participatory analysis of problems, (2) paradigm shifting, (3) conducting workshops; and (4) setting determination and motivation for health promotion. The participation of study subjects in the process was ensured. After the model implementation, a significant decline of various risk indicators were observed among the participants (p<0.05). The so-called APPC model was comprised of 4 essential components: (1) analysis of the problems through participatory process, (2) analysis of the problems through participatory process, (2) paradigm adjustment, (3) participatory workshops, and (4) commitment and encouragement. Thus, the model should be routinely promoted in educational settings through an integration within health promotion curriculum, with participation of both faculty staff and students.